Large Universe CCA2 CP-ABE With Equality and Validity Test in the Standard Model. (17th July 2020) - Li, Cong; Shen, Qingni; Xie, Zhikang; Feng, Xinyu; Fang, Yuejian; Wu, Zhonghai
Abstract: Attribute-based encryption with equality test (ABEET) simultaneously supports fine-grained access control on the encrypted data and plaintext message equality comparison without decrypting the ciphertexts. Recently, there have been several literatures about ABEET proposed. Nevertheless, most of them explore the ABEET schemes in the random oracle model, which has been pointed out to have many defects in practicality. The only existing ABEET scheme in the standard model, proposed by Wang et al., merely achieves the indistinguishable against chosen-plaintext attack security. Considering the aforementioned problems, in this paper, we propose the first direct adaptive chosen-ciphertext security ciphertext-policy ABEET scheme in the standard model. Our method only adopts a chameleon hash function and adds one dummy attribute to the access structure. Compared with the previous works, our scheme achieves the security improvement, ciphertext validity check and large universe. Besides, we further optimize our scheme to support the outsourced decryption. Finally, we first give the detailed theoretical analysis of our constructions in computation and storage costs, then we implement our constructions and carry out a series of experiments. Both results indicate that our constructions are more efficient in Setup and Trapdoor and have the shorter public parameters than the existing ABEET ones do.